Evaluation of ionic degradation and slot corrosion of metallic brackets by the action of different dentifrices - BRANDÃO, Gustavo Antônio Martins (2015)
OBJECTIVE: To evaluate the in vitro ionic degradation and slot base corrosion of metallic brackets subjected to brushing with dentifrices, through analysis of chemical composition by Energy Dispersive Spectroscopy (EDS) and qualitative analysis by Scanning Electron Microscopy (SEM). METHODS: Thirty eight brackets were selected and randomly divided into four experimental groups (n = 7). Two groups (n = 5) worked as positive and negative controls. Simulated orthodontic braces were assembled using 0.019 x 0.025-in stainless steel wires and elastomeric rings. The groups were divided according to surface treatment: G1 (Máxima Proteção Anticáries®); G2 (Total 12®); G3 (Sensitive®); G4 (Branqueador®); Positive control (artificial saliva) and Negative control (no treatment). Twenty eight brushing cycles were performed and evaluations were made before (T0) and after (T1) experiment. RESULTS: The Wilcoxon test showed no difference in ionic concentrations of titanium (Ti), chromium (Cr), iron (Fe) and nickel (Ni) between groups. G2 presented significant reduction (p < 0.05) in the concentration of aluminium ion (Al). Groups G3 and G4 presented significant increase (p < 0.05) in the concentration of aluminium ion. The SEM analysis showed increased characteristics indicative of corrosion on groups G2, G3 and G4. CONCLUSION: The EDS analysis revealed that control groups and G1 did not suffer alterations on the chemical composition. G2 presented degradation in the amount of Al ion. G3 and G4 suffered increase in the concentration of Al. The immersion in artificial saliva and the dentifrice Máxima Proteção Anticáries® did not alter the surface polishing. The dentifrices Total 12®, Sensitive® and Branqueador® altered the surface polishing.